2008
DOI: 10.1128/jvi.00147-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Physical Interactions of the Herpes Simplex Virus Type 1 UL20 Membrane Protein with Glycoprotein K

Abstract: Herpes simplex virus type 1 glycoprotein K (gK) and the UL20 protein (UL20p) are coordinately transported to the trans-Golgi network (TGN) and cell surfaces and are required for cytoplasmic virion envelopment at the TGN. In addition, cell surface expression of gK and UL20p is required for virus-induced cell fusion. Previously, confocal microscopy colocalization and intracellular transport experiments strongly suggested direct proteinprotein interactions between gK and UL20p. Direct protein-protein interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…Alphaherpesvirus capsid-membrane association and envelopment are driven by numerous cooperative, and in some cases redundant, interactions between multiple tegument and envelope proteins (8)(9)(10)(11)(12)(13)73) and the cellular ESCRT machinery (14)(15)(16)(17)(18)(19). While it is clear that UL36p is essential for envelopment, the simplest interpretation of our data is that the association of some HSV capsids with the surface of cytoplasmic organelles does not absolutely require UL36p.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Alphaherpesvirus capsid-membrane association and envelopment are driven by numerous cooperative, and in some cases redundant, interactions between multiple tegument and envelope proteins (8)(9)(10)(11)(12)(13)73) and the cellular ESCRT machinery (14)(15)(16)(17)(18)(19). While it is clear that UL36p is essential for envelopment, the simplest interpretation of our data is that the association of some HSV capsids with the surface of cytoplasmic organelles does not absolutely require UL36p.…”
Section: Discussionmentioning
confidence: 67%
“…These naked cytoplasmic capsids subsequently undergo secondary envelopment at a postnuclear organelle to assemble the mature, infectious virion (4-9). Completion of cytoplasmic envelopment requires the coordinated interaction of multiple virally encoded proteins (8,(10)(11)(12)(13) and the participation of components of the cellular endosomal sorting complexes required for transport (ESCRT) machinery (14-19).UL36p (VP1/2) is the largest structural protein encoded by the herpesviridae (20, 21). It is a major constituent of the innermost layer of tegument, the complex protein layer between the capsid and the inner surface of the envelope, and connects the capsid to multiple outer tegument proteins (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gK expressed on virions forms a complex with the membrane-associated UL20 viral protein (52,56). HSV-1 mutants that lack gK fail to acquire a cytoplasmic envelope efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that HSV-1 gK and UL20 functionally and physically interact, and this interaction is mandatory for their coordinated intracellular transport, cell surface expression, and functions in virion egress, virus-induced cell fusion, and virus entry (18)(19)(20)(21). Recently, we showed that the amino terminus of gK interacts with gB and gH and can complement gB-mediated cell fusion (22,23).…”
mentioning
confidence: 99%